The Basic Income as a Possible Instrument of Personal, Family and Labor Reconciliation - Carrero Domínguez, Carmen (2016)
The present paper will analyze, in the first place, the state of reconciliation of work, personal and family life, pointing those deficiencies that are presented, and the obstacles on the development of this right. Additionally, it will analyze if the establishment of a basic income could be an incentive to this reconciliation or, to the contrary, it could have an adverse effect, this seen from a gender perspective.